POLITICS AS A REQUIREMENT. ON THE CONCEPT OF HUMAN RIGHTS AND THE RIGHT TO AN AUTOBIOGRAPHY AS AN ETHICAL CATEGORY - Villalobos, Jose Vicente (Opción, 2019)
To speak of democracy today implies having an idea of the evolution of law as a guarantee for its exercise. Nobody can express himself around the elements that constitute it without making references to its fundamental structure, that is, the right to an autobiography. Let us see what is meant by such.